Development of Module Learning Based on Concept with Exampel on Cell Material for Students SMA - Meli Gustinasari; Lufri Lufri; Ardi Ardi (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2017)
The purposes of this research are to result and show the validity and practicality of biology module based on concept with example on cell material for Senior High School students. This research used 3 steps from AP3 Models those are problem and necessary analize, design, and develop. The subjects of this research were 5 validators, 2 teachers, and 20 students class XI from MAN 3 Padang. Data in this research was primary data collected from validity and practicality questionnaire. The result of validity was 86,31% in criteria valid, practicality by teachers was 87,50% in criteria practice, and practicality by students was 87,59% in criteria practice.